2020
DOI: 10.2139/ssrn.3636640
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of the Economics of Covid-19

Abstract: The goal of this piece is to survey the developing and rapidly growing literature on the economic consequences of COVID-19 and the governmental responses, and to synthetize the insights emerging from a very large number of studies. This survey: (i) provides an overview of the data sets and the techniques employed to measure social distancing and COVID-19 cases and deaths; (ii) reviews the literature on the determinants of compliance with and the effectiveness of social distancing; (iii) the macroeconomic and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
104
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(111 citation statements)
references
References 84 publications
0
104
0
7
Order By: Relevance
“…COVID-19 also affected the countries’ GDPs to a great extent. For example, the UK’s GDP falls by 21.7% during the second quarter due to COVID-19, with and is second to Spain with a GDP decline of 22.1% (Brodeur et al, 2021; Magzter, 2020; Shah et al, 2021; Noor et al, 2020b). Similarly, the COVID-19 is hitting firms hard and adversely affecting firms’ operations, greatly reducing their profits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…COVID-19 also affected the countries’ GDPs to a great extent. For example, the UK’s GDP falls by 21.7% during the second quarter due to COVID-19, with and is second to Spain with a GDP decline of 22.1% (Brodeur et al, 2021; Magzter, 2020; Shah et al, 2021; Noor et al, 2020b). Similarly, the COVID-19 is hitting firms hard and adversely affecting firms’ operations, greatly reducing their profits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The experience of mental health problems is disproportionate across groups, by gender, age, race, and socioeconomic status. Groups with disadvantaged backgrounds such as lower socioeconomic positions and pre‐existing psychological distress were more likely to experience adversities including job loss and financial stress, and difficulties accessing basic requirements like food and medical care (Brodeur et al., 2021; Pierre et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, higher epidemic incidence depresses aggregate demand, which lowers the contact rate and reduces infections. Furthermore, some recent studies have shown that human movement patterns are strongly associated with regional socioeconomic indicators Avery et al [4], Basurto et al [7], Brodeur et al [13], Papageorge et al [55]. In particular, direct and indirect e ects of lockdown measure has trigger economical sequential adjustment process in response to shocks to productive capacity (supply shocks) and/or to nal demand (demand shocks).…”
Section: Literature Reviewmentioning
confidence: 99%